Pengaruh Brand Image dan Pemasaran Digital terhadap Minat Beli Konsumen pada Produk Nestle : (Studi Kasus Brastagi Supermarket Tiara) - Winna Triwahyuni Tanjung; Amirudin Amirudin; Mella Yunita (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The purpose of this study was to determine the Influence of Brand Image and Digital Marketing on Consumer Purchase Interest in Nestle Products (Case Study of Brastagi Supermarket Tiara). This study was conducted at Brastagi Supermarket Tiara with a population and sample of 100 consumers. The research instrument was a questionnaire with a Likert scale model. The requirement test was carried out to test normality. The data analysis technique used was the Multiple Regression technique at a significance level of a = 0.05. The results of this study indicate that Brand Image (X1) has a significant effect on Consumer Purchase Interest in Nestle Products at Brastagi Supermarket Tiara, the calculated t is greater than the t table (2.903 ˃ 1.660) with a significant value of 0.000. While Digital Marketing (X2) has a significant effect on Consumer Purchase Interest in Nestle Products at Brastagi Supermarket Tiara with a calculated t value greater than the t table (2.678 ˃ 1.660) with a significant value of 0.000. Based on the output of SPSS Version 25, it is known that the Rsquared value is 0.177, meaning that the variance of the Purchase Interest variable can be explained by the Brand Image and Digital Marketing variables by 17.7%, while the rest is explained by other variables not included in this model. In other words, there are still other independent variables that affect Purchase Interest.